The Multifaceted Mechanism of Leptin Signaling within Tumor Microenvironment in Driving Breast Cancer Growth and Progression - Andò, Sebastiano (Front Oncol, 2014)
Adipokines represent likely candidates to mediate the increased breast cancer risk and the enhanced progression associated with obesity. Other contributors to obesity-related cancer progression are insulin/IGF-1 pathways and hormones. Among these, the adipokine leptin is the most intensively studied in both metabolism in general and in cancer due to the fact that leptin levels increase in proportion of fat mass. Leptin is primarily synthesized from adipocytes but it is also produced by other cells including fibroblasts. In this latter case, it has been well demonstrated how cancer-associated fibroblasts express leptin receptor and secrete leptin, which sustains a short autocrine loop and is able to target tumor epithelial cells enhancing breast cancer cell motility and invasiveness. In addition, it has been reported that leptin may induce breast cancer to undergo a transition from epithelial to spindle-like mesenchymal morphology, activating the signaling pathways devoted to the EMT. Thus, it emerges how leptin may play a crucial role in mediating malignant cell and tumor microenvironment interactions. Here, we present an overview of the role of leptin in breast cancer, covering the following topics: (1) leptin as an amplifier of estrogen signaling in tumor epithelial cells contributing to the promotion of carcinogenesis; (2) leptin as a crucial player in mediating tumor-stroma interaction and influencing EMT-linked mechanisms, that may sustain breast cancer growth and progression; (3) leptin and leptin receptor targeting as novel therapeutic strategies for breast cancer treatment.